Candidalysin Crucially Contributes to Nlrp3 Inflammasome Activation by Candida albicans Hyphae - Ona Rogiers (American Society for Microbiology, 2019)
ABSTRACT Candida albicans is an opportunistic fungal pathogen that can cause life-threatening infections, particularly in immunocompromised patients. C. albicans induced activation of the Nlrp3 inflammasome, leading to secretion of bioactive interleukin 1β (IL-1β) is a crucial myeloid cell immune response needed for antifungal host defense. Being a pleiomorphic fungus, C. albicans can provoke Nlrp3 inflammasome responses only upon morphological transformation to its hyphal appearance. However, the specific hyphal factors that enable C. albicans to activate the Nlrp3 inflammasome in primary macrophages remain to be revealed. Here, we identify candidalysin, a peptide derived from the hypha-specific ECE1 gene, as a fungal trigger for Nlrp3 inflammasome-mediated maturation and secretion of IL-1β from primary macrophages. Direct peptide administration experiments showed that candidalysin was sufficient for inducing secretion of mature IL-1β from macrophages in an Nlrp3 inflammasome-dependent manner. Conversely, infection experiments using candidalysin-deficient C. albicans showed that candidalysin crucially contributed to the capacity of this fungus to induce maturation and secretion of IL-1β from primary macrophages. These complementary observations identify the expression of candidalysin as one of the molecular mechanisms by which hyphal transformation equips C. albicans with its proinflammatory capacity to elicit the release of bioactive IL-1β from macrophages. IMPORTANCE Candidiasis is a potentially lethal condition that is caused by systemic dissemination of Candida albicans, a common fungal commensal residing mostly on mucosal surfaces. The transition of C. albicans from an innocuous commensal to an opportunistic pathogen goes hand in hand with its morphological transformation from a fungus to a hyphal appearance. On the one hand, the latter manifestation enables C. albicans to penetrate tissues, while on the other hand, the expression of many hypha-specific genes also endows it with the capacity to trigger particular cytokine responses. The Nlrp3 inflammasome is a crucial component of the innate immune system that provokes release of the IL-1β cytokine from myeloid cells upon encountering C. albicans hyphae. Our study reveals the peptide candidalysin as one of the hypha-derived drivers of Nlrp3 inflammasome responses in primary macrophages and, thus, contributes to better understanding the fungal mechanisms that determine the pathogenicity of C. albicans.